Open Protocols, the new standard for acoustic tracking: results from interoperability and performance tests in European waters - Eneko Aspillaga; Stijn Bruneel; Josep Alós; Pieterjan Verhelst; David Abecasis; Kim Aarestrup; Kim Birnie-Gauvin; Pedro Afonso; Miquel Palmer; Jan Reubens (Animal Biotelemetry)
Abstract Background The lack of compatibility between acoustic telemetry equipment from different manufacturers has been a major obstacle to consolidating large collaborative tracking networks. Undisclosed encrypted signal coding protocols limit the use of acoustic telemetry to study animal movements over large spatial scales, reduce competition between manufacturers, and stifle innovation. The European Tracking Network, in collaboration with several acoustic telemetry manufacturers, has worked to develop new transparent protocols for acoustic tracking. The results are energy-efficient transmission protocols accessible to all researchers and manufacturers. Today, the Open Protocols (OP) are already available to manufacturers and developers, and the first transmitters and receivers to implement them are already in the water. Results The main objective of this study was to confirm the compatibility between devices from different manufacturers using OP, characterise the acoustic range of each transmitter–receiver manufacturer combination, compare the detection efficiency to the standard protocols used at present (R64K and encrypted protocols), and assess its robustness against spurious detections. An international collaborative effort was made to conduct acoustic range tests in four main aquatic habitats: a river, a coastal lagoon, a coastal habitat, and the open sea. Receivers and transmitters from different manufacturers were deployed at increasing distances from each other using the same experimental design at each location. The decay of detection probability with distance was modelled for each transmitter–receiver manufacturer combination by applying logistic regression using a Bayesian approach. Furthermore, to thoroughly assess performance differences in an applied research context, we conducted a direct field comparison between groups of smolts tagged with OP and R64K tags, tracking their migration to the sea. Conclusions Our results confirm full compatibility between the tested devices, with negligible differences in the measured acoustic ranges between OP manufacturers and when compared to encrypted protocols. The OP was also robust against spurious detections, and the field comparison between OP and R64K showed equal performance. We hope these novel insights will encourage international research groups to promote OP-based studies to ensure compatibility and maximise the benefits of acoustic telemetry networks.